INFANT MORTALITY IN NUAULU AND NON-NUAULU COMMUNITIES IN MALUKU TENGAH: Social Exclusion And Ethnicity In Indonesia - Anita S. Wartaman; Raldi H. Koestoer (Research Centre for Population, Indonesian Institute of Sciences, 2007)
Investment Climate is one of the crucial issues in the country as stated in the White Paper and President Decree No 87of 2003. Through investment, it is expected the employment is encouraged the national economy. This paper focusses on two major points, firstly, characteristics of investment in post crisis program and, secondly, how it impacts on employment in the regions oflndonesia, especially in West and Eastern Indonesia with certain quality in human resources. The outcomes indicate that the diversity of regional investment and labour absorption with specific quality ofhuman resources. The former refers to regional variations and the latter gives the impacts on employment with specific level on human quality resources. There would be a significant difference between West and Eastern Indonesia to impose the impact of investment inductions in several areas with specific patterns emerge.Keywords: Investasi; Kesempatan kerja; Kualitas sumber daya manusia; Indonesia Bagian Barat; Indonesia Bagian Timur